De Jeanne D'Arc à Madeleine de Verchères: la femme guerrière dans la société d'Ancien Régime - Gervais, Diane; Lusignan, Serge (Revue d'histoire de l'Amérique française, 1999)
issued: 1999-23-00
Keywords: Combat; Femmes; Forts

Les habitants de Lachine et le massacre de 1689 - Lamarche, Hélène (Mémoires de la Société généalogique canadienne-française, 1999)
issued: 1999-23-00
Keywords: Lachine

Pierre Le Moyne d'Iberville - Lamarche, Jacques (Lidec, 1999)
Keywords: Le Moyne d'Iberville et d'Ardillières; Pierre

Entente cordiale? La section montréalaise du Fonds patriotique canadien, 1914-1923: le bénévolat de guerre à Montréal - Morton, Desmond (Revue d'histoire de l'Amérique française, 1999)
issued: 1999-23-00
Keywords: Bénévolat; Guerre

GREENSHIELDS, EDWARD BLACK - Burr, Gordon (Dictionnaire biographique du Canada, 1998)

LACHAPELLE, SÉVERIN - Desjardins, Rita (Dictionnaire biographique du Canada, 1998)

LACHAPELLE, EMMANUEL-PERSILLIER - Desrosiers, George; Gaumer, Benoît; Keel, Othmar (Dictionnaire biographique du Canada, 1998)

Bagarres entre militaires et "zoot-suiters" survenues à Montréal et à Verdun en juin 1944: problème de langue, de relations entre civils et militraires ou de rébellion juvénile? - Durflinger, Serge Marc (L'impact de la Deuxième Guerre mondiale sur les sociétés canadienne et québécoise, 1998)
Keywords: Armée; Vêtements

The Romance of Reunion: Montreal War Veterans Return to Family Life, 1944-1949 - Fahrni, Magda (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1998)
Number: 1
Keywords: Famille; Guerre

Les quatre couleurs de Radisson: explorer aujourd'hui le XVIIe siècle - Fournier, Martin (Université Laval, 1998)

GIRDWOOD, GILBERT PROUT - Goulet, Denis (Dictionnaire biographique du Canada, 1998)

Pièges de la mémoire: Dollard Des Ormeaux. Les Amérindiens et nous - Groulx, Patrice (Vents d'Ouest, 1998)
Keywords: Autochtones; Dollard Des Ormeaux; Adam

BURLAND, JEFFREY HALE - Keating, Peter (Dictionnaire biographique du Canada, 1998)

HÉBERT, LOUIS-PHILIPPE - Lacasse, Yves (Dictionnaire biographique du Canada, 1998)

BOUCHER DE BOUCHERVILLE, sir CHARLES - Munro, Kenneth (Dictionnaire biographique du Canada, 1998)

OUIMET, JOSEPH-ALDRIC - Munro, Kenneth (Dictionnaire biographique du Canada, 1998)

McCRAE, JOHN - Prescott, John F. (Dictionnaire biographique du Canada, 1998)

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

Les habits rouges et les Patriotes - Senior, Elinor Kyte (VLB, 1997)
Keywords: Britanniques; Rébellions

Les relations entre Le Devoir et les censeurs de la presse pendant la Seconde Guerre mondiale - Beauregard, Claude (Le Devoir: un journal indépendant, 1910-1995, 1996)
Keywords: Devoir (Le); Guerre

Les milieux d'affaires francophones de Montréal face à la Première Guerre mondiale - Villerbu, Tangi (Université de Rennes 2, 1996)
Keywords: Francophones; Guerre; Hommes d'affaires

Guerre et censure: l'expérience des journaux, des militaires et de la population pendant la Deuxième Guerre mondiale - Beauregard, Claude (Université Laval, 1995)
Keywords: Guerre; Journalistes

Les drapeaux militaires en Nouvelle-France - Chartrand, René (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Number: 1
Keywords: Armée

La consommation de viande à Montréal au XVIIe et au XVIIIe siècles - Cossette, Évelyne (Archéologies québécoises, 1995)
Keywords: Alimentation; Auberges; Champ-de-Mars; Fortifications; Hôpital Général; Hôpitaux; Place Royale; Places publiques; Wurtele; Jacob

La fin des alliances franco-indiennes: enquête sur un sauf-conduit de 1760 devenu un traité en 1990 - Vaugeois, Denis (Boréal, 1995)
Keywords: Autochtones; Français

OGILVIE, ALEXANDER WALKER - Brassard, Michèle; Hamelin, Jean (Dictionnaire biographique du Canada, 1994)

Le mouvement ouvrier montréalais et la crise de la conscription 1916-1918 - Dansereau, Bernard (Université du Québec à Montréal, 1994)
Keywords: Conscription; Guerre

La nature des attaques iroquoises contre Ville-Marie, 1642-1667 - Gélinas, Claude (Recherches amérindiennes au Québec, 1994)
issued: 1994-21-00
Keywords: Autochtones; Iroquois

CAMPBELL, FRANCIS WAYLAND - Milner, Elizabeth Hearn (Dictionnaire biographique du Canada, 1994)

LAVIGNE, ERNEST - Poirier, Lucien (Dictionnaire biographique du Canada, 1994)

La région de Montréal face au déclin des dépenses militaires - Bélanger, Yves (Cahiers de géographie du Québec, 1993)
Number: 102
Keywords: Armée

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger; Jacques

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

Les fortifications de Montréal - Charbonneau, André; Lafrance, Marc; Poirier, Monique (Montréal, ville fortifiée au XVIIIe siècle, 1992)
Keywords: Fortifications

Montréal: Entrepôt and Military Logistics Centre - Charbonneau, André; Lafrance, Marc; Poirier, Monique (Opening the Gates of Eighteenth-Century Montréal, 1992)
Keywords: Armes; Armée

Montréal: entrepôt militaire et centre logistique - Charbonneau, André; Lafrance, Marc; Poirier, Monique (Montréal, ville fortifiée au XVIIIe siècle, 1992)
Keywords: Armes; Armée

The Fortifications of Montreal - Charbonneau, André; Lafrance, Marc; Poirier, Monique (Opening the Gates of Eighteenth-Century Montréal, 1992)
Keywords: Fortifications

Une place de guerre - Chartrand, René (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

La paix de Callière - de Lagrave, Jean-Paul (Cap-aux-Diamants, 1992)
issued: 1992-24-00

Vivre en Canada - Dickinson, John (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

De la Nouvelle-Angleterre à la Nouvelle-France: l'histoire des captifs anglo-américains au Canada entre 1675 et 1760 - Fournier, Marcel (Société généalogique canadienne-française, 1992)
Keywords: Américains; Captifs

La Grande Paix de Montréal de 1701: les voies de la diplomatie franco-amérindienne - Havard, Gilles (Recherches amérindiennes au Québec, 1992)
Keywords: Autochtones; Français; Grande Paix de Montréal

Une assemblée de 1300 ambassadeurs - Landry, Yves (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

The Fortifications of Montreal 1717-1744: the Development and Implementation of the Plan - Poirier, Monique (Université Concordia, 1991)
Keywords: Fortifications

BELLINGHAM, SYDNEY ROBERT - Daley, Robert C. (Dictionnaire biographique du Canada, 1990)

DESBARATS, GEORGE-ÉDOUARD - Galarneau, Claude (Dictionnaire biographique du Canada, 1990)

OGILVIE, WILLIAM WATSON - Levine, Allan (Dictionnaire biographique du Canada, 1990)

The Montreal Militia as a Social Institution before World War I - Miller, Carman (Urban History Review / Revue d'histoire urbaine, 1990)
Number: 1
Keywords: Milice

KINGSFORD, WILLIAM - Taylor, M. Brook (Dictionnaire biographique du Canada, 1990)